2023
DOI: 10.1186/s40561-023-00242-0
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the usability of Tinkercad application in educational robotics teaching by eye tracking technique

Abstract: Like all sectors, the education sector has been negatively affected by the Covid-19 pandemic. Considering the decision to conduct face-to-face training in schools remotely, teachers had many difficulties in moving course content to the online platform. Teachers who perform robotic coding applications are looking for ways to do these activities remotely. Simulators enable real objects to be animated in a computer environment. There are many paid and free platforms that simulate robotic coding tools. Arduino and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Research by Erdogan et al has shown that eye tracking can provide valuable insights into users' cognitive processes and engagement levels. By analyzed eye movements, educators can better understand how students interact with the platform, leading to improvements in design and instructional strategies (Erdogan et al 2023). Zhao et al (2014) investigated differences in reading strategies using eye-tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Erdogan et al has shown that eye tracking can provide valuable insights into users' cognitive processes and engagement levels. By analyzed eye movements, educators can better understand how students interact with the platform, leading to improvements in design and instructional strategies (Erdogan et al 2023). Zhao et al (2014) investigated differences in reading strategies using eye-tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen defines usability as a quality attribute that evaluates the usability of a user interface [15] and as one method that not only improves ease of use during the design process but also assesses how easy the user interface is to use [16]. Usability according to Nielsen is also a general method based on examining design interfaces [17]. The Nielsen model is more acceptable for measuring usability because the structure of quality characteristics is described more systematically and the place of use is clearly defined [15].…”
Section: Introductionmentioning
confidence: 99%
“…Eye tracking-for attention recognition and state detection, by assessment of some parameters [15], e.g., pupil dilation [16,17], saccade and fixation duration [18]; • Facial expression recognition-for emotional and cognitive state detection [19][20][21]; • Electrocardiography (ECG), electrodermal activity (EDA) [22][23][24][25][26], and skin temperature sensors [27]-for assessment of the human body's physiological reactions related to stress, anxiety, agitation, cognitive load, etc. It was also shown that the detection of heart rate variability could be based on photoplethysmography (PPG) sensors integrated into wearable devices [28,29], as well as on traditional electrode-based technology integrated into plasters [30] or smart textiles [31,32]; • Electroencephalography (EEG) [33][34][35][36][37][38]-for capturing the cognition processes, even in cases of a lack of behavioral reaction caused by a specific stimulus.…”
mentioning
confidence: 99%